A consistent mass and momentum flux computation method for two phase flows. Application to atomization process. (18th July 2017) - Vaudor, G.; Ménard, T.; Aniszewski, W.; Doring, M.; Berlemont, A.
Highlights: Consistent mass and momentum flux computation in CLSVOF approach. New method to evaluate all mass fluxes in MAC approach. Great improvement of the momentum flux calculation in all test cases. Abstract: This paper presents a new computational method for consistent calculation of mass and momentum fluxes in a two-phase flow simulation. The problem of inconsistency of the mass and momentum transfers has been long known in the two-phase flow context. Once the density ratio between fluid phases becomes high, and/or the momentum of one phase differs significantly from that of the other, a decoupling phenomenon causes a non-physical transfer of momentum, rendering most codes unstable. Original works of Rudman [31] have addressed this by proposing a way to couple the mass and momentum flux transport. To ensure this consistency between both fluxes in a staggered configuration, Rudman introduces a finer sub-grid to transport the volume of fluid. In our paper, we present a way to adopt Rudman's approach without this subgrid, but always in a stagerred grid. The method is presented along with validation test cases and example applications, including very demanding momentum-dominated 3D simulations.